Coastline Mapping In Pati District Utilising Landsat-8 Satellite Images In 2015-2024 - Alfiandi Setya Dwinanda; Hendrata Wibisana (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The coastline changes from time to time in line with natural changes such as wave activity, and sediment. This study aims to determine the changes in coastline on the coast of Pati Regency in 2015-2024. The research method utilises Geographic Information System (GIS) and remote sensing technology by taking Landsat-8 satellite image data processed using ArcGis application then calculated using Haversin Formula and Euclidean Distance calculation. The results showed that the largest shoreline change was found in transect 3 located in Dukuhseti Subdistrict, Kembang Village with a value of 453.92 metres within 10 years and the smallest shoreline change value occurred in transect 8 located in Tayu Subdistrict, Tunggulsari Village with a change value of 2.41 metres within 10 years.